2017
DOI: 10.1007/s10787-017-0311-x
|View full text |Cite
|
Sign up to set email alerts
|

A combination of probiotics and magnesium orotate attenuate depression in a small SSRI resistant cohort: an intestinal anti-inflammatory response is suggested

Abstract: Approximately, one-third of those who develop major depression will have a poor response to treatment and over time can become treatment resistant. Intestinal dysbiosis has been implicated in depression with systemic inflammation and vagal and enteric nerve impairment. We report on a sequel pilot study (n = 12) with a combination probiotics/magnesium orotate formulation adjuvant administered with SSRIs for treatment resistant depression. At the end of an 8-week intervention mean changes for depression scores a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 12 publications
1
57
0
3
Order By: Relevance
“…In a study with treatment resistant MDD patients, 8 weeks supplementation with Lactobacillus acidophilus , Bifidobacterium bifidum , Streptoccocus thermophiles and magnesium orotate reduced depression scores and improved life quality . Similarly, the administration of Lactobacillus acidophilus , Lactobacillus casei , and Bifidobacterium bifidum decreased depression scores, and high sensitivity CRP, while increasing glutathione levels .…”
Section: How Can We Leverage the Mgib Axis In The Treatment Of Mdd?mentioning
confidence: 95%
“…In a study with treatment resistant MDD patients, 8 weeks supplementation with Lactobacillus acidophilus , Bifidobacterium bifidum , Streptoccocus thermophiles and magnesium orotate reduced depression scores and improved life quality . Similarly, the administration of Lactobacillus acidophilus , Lactobacillus casei , and Bifidobacterium bifidum decreased depression scores, and high sensitivity CRP, while increasing glutathione levels .…”
Section: How Can We Leverage the Mgib Axis In The Treatment Of Mdd?mentioning
confidence: 95%
“…Therefore, certain probiotics may serve as an adjuvant or alternative treatment for MDD and its subtypes. A pilot study showed that MSP, together with a magnesium supplement, decreased depression in SSRI treatment-resistant patients (Bambling et al, 2017). A clinical trial also reported that the combination of B. longum and L. helveticus decreased depression in MDD patients with prior use of standard antidepressants (Kazemi et al, 2019).…”
Section: Heterogeneity Of Depressionmentioning
confidence: 99%
“…However, MSPs may have higher potency in humans. In MDD patients, SSP (L. plantarum) did not reduce depression but improved cognition (Lew et al, 2018), whereas MSPs had repeatedly shown antidepressive efficacy (Akkasheh et al, 2016;Bambling et al, 2017;Ghorbani et al, 2018;Kazemi et al, 2019). MSPs often gave better therapeutic efficacy compared to that of SSPs in gut-related disorders and pathogen infections, which could be explained by an overall higher dosage (Chapman et al, 2011(Chapman et al, , 2012.…”
Section: Single-species and Multi-species Probioticmentioning
confidence: 99%
“…Although mild depression can be treated with various medicines, major depressive disorder (MDD) is difficult to treat. 5 Additional pharmacotherapy prescriptions include anti-psychiatric agents that can produce severe side-effects. 1 The severity of MDD is caused by physical illnesses such as cardiovascular disorders, stroke, metabolic syndromes, and psychiatric conditions such as anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] For example, it has been shown that the Bacteroides genus in patients with MDD was increased, while the Lachnospiraceae genus was decreased. 5,14,15 Further consideration on the mechanisms central to the role that gut microorganisms may have on the pathogenesis of MDD is of significant importance. Emerging evidence with the administration of probiotics has demonstrated a decrease in neuroinflammation, a pathogenic characteristic of depression.…”
Section: Introductionmentioning
confidence: 99%